Solar retinopathy related to antidepressant use in a patient with major depressive disorder: a case report - Eun-Jin Cheon (Journal of Yeungnam Medical Science, 2024)
This case report is a unique case of solar retinopathy following antidepressant-induced mydriasis and highlights the need for comprehensive ophthalmic evaluation in patients treated with medications having mydriatic effects. A 49-year-old female patient who had received long-term antidepressant therapy presented with bilateral visual impairment after prolonged sun exposure. Fundoscopy confirmed solar retinopathy, which was attributed to drug-induced mydriasis. Medication adjustments and sun protection strategies led to full visual recovery, underscoring the importance of interdisciplinary awareness. This case emphasizes the challenges associated with the simultaneous management of psychiatric and ophthalmic conditions and highlights the need for routine ophthalmic evaluation of patients prescribed antidepressants with reported ocular side effects.